2022
DOI: 10.3390/biology11040541
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia In Vivo Induces Cardiolipin Oxidation in Rat Kidney Mitochondria

Abstract: Cardiolipin is a mitochondrial phospholipid that plays a significant role in mitochondrial bioenergetics. Cardiolipin is oxidized under conditions like oxidative stress that occurs during ischemia/reperfusion; however, it is known that even during ischemia, many reactive oxygen species are generated. Our aim was to analyze the effect of in vivo ischemia on cardiolipin oxidation. Adult male Wistar rats were anesthetized; then, their abdomens were opened, and microvascular clips were placed on renal arteries for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Cardiolipins are highly susceptible to oxidation because of their unique location near the site of ROS generation and the presence of unsaturated fatty acids [ 39 , 41 ]. Several studies have shown that peroxidation of cardiolipin increases following ischemia/reperfusion injury [ 42 , 43 ]. In line with the previous results, our study demonstrated that cardiolipin peroxidation increases following H/R injury in H9c2 cardiomyocytes, and BMX-001 protects cardiolipin against oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiolipins are highly susceptible to oxidation because of their unique location near the site of ROS generation and the presence of unsaturated fatty acids [ 39 , 41 ]. Several studies have shown that peroxidation of cardiolipin increases following ischemia/reperfusion injury [ 42 , 43 ]. In line with the previous results, our study demonstrated that cardiolipin peroxidation increases following H/R injury in H9c2 cardiomyocytes, and BMX-001 protects cardiolipin against oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Separation and investigation of individual cardiolipin forms was performed by ultra-effective liquid chromatography—tandem mass spectrometry (UPLC-MS/MS) using Waters Acquity UPLC chromatography system coupled with a Xevo TQD (triple quadrupole) mass spectrometer (Waters, Milford, MA, USA) as described before [ 60 ]. Data was analyzed using MassLynx V4.1.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial dysfunction, caused by DNA damage or environmental stresses, leads to intrinsic mitochondrial diseases and degenerative diseases. , Cardiolipin (CL) is an essential phospholipid for the unique cristae structure of the mitochondrial inner membrane . Accumulating evidence suggests that mitochondrial dysfunction can result from the destruction of cristae structure due to CL remodeling. CL, located exclusively in the inner membrane of mitochondria (IMM), is composed of two phosphate and four fatty acid moieties and plays a crucial role in maintaining proper protein complex function by inducing negative curvature and ensuring membrane structure stability . Pathological CL remodeling, induced by peroxidation and CL content reduction, leads to membrane leakage and a loss of function of IMM protein complexes.…”
Section: Introductionmentioning
confidence: 99%